Physical and electrical properties of molybdenum thin films grown by DC magnetron sputtering for photovoltaic application - Rashid, Haroon; Rahman, Kazi Sajedur; Hossain, Mohammad Istiaque; Nasser, Ammar Ahmed; Alharbi, Fahhad H.; Akhtaruzzaman, Md.; Amin, Nowshad (Elsevier, 2019)
DC magnetron sputtering was utilized to grow thin layers of molybdenum (Mo) on top of soda lime glass substrates. Deposition power was varied for suitable characteristics of films grown at various DC powers, i.e. 100 W, 150 W and 200 W. Thin Mo film of approximately 580 nm thickness was successfully grown at DC power of 100 W at room temperature. Structural, morphological, electrical and optical properties of Mo thin films were analyzed. XRD patterns revealed Mo films to be monocrystalline in nature and only one peak was observed corresponding to the (1 1 0)cub reflection plane at 2θ = 40.5°. Exceptionally dense microstructure was found for surface morphology observation by AFM and FESEM. Increasing deposition power resulted in coarser surface of the grown films. The minimum average surface roughness was found to be around 0.995 nm. Scotch tape adhesion test was performed to validate adhesion. Grown Mo films were found metallic in nature with electrical resistivity of 2.64 × 10−5 Ω-cm. Furthermore, it was found that by increasing deposition power, the electrical resistivity could further be reduced. © 2019